Study of biofilm formation in bacterial isolates from contact lens wearers - L Raksha; Nagaraju Gangashettappa; G B Shantala; Bhavna R Nandan; Deepa Sinha (Indian Journal of Ophthalmology, 2020)
Purpose: To detect biofilm forming capacity of bacterial isolates obtained from the conjunctiva, contact lens and accessories of contact lens wearers using phenotypic and genotypic methods. Methods: Bacterial strains were collected from the conjunctiva, contact lens and lens storage cases of contact lens wearers. The phenotypic detection of biofilm production was done using the tube method and congo red agar method. The biofilm-forming related genes, icaA, of Coagulase negative Staphylococcus (CONS) and Staphylococcus aureus, and pslA, of P. aeruginosa, were detected using PCR. Results: A total of 265 bacterial isolates which included S. aureus, CONS, Pseudomonas, Nil-fermenter Gram-negative bacilli (NFGNB), Bacillus spp, Diphtheroids, Micrococci, Klebsiella pneumonia, Klebsiella oxytoca, E. coli, Proteus mirabilis, Proteus vulgaris, Citrobacter koseri, Citrobacter freundii, Enterobacter cloacae, Moraxella were obtained. Of the 265 isolates, 53.5% were moderately positive, 33.2% strongly positive and 13.2% negative for biofilm production by tube method and 36.6% were moderately positive, 40% strongly positive and 23.3% negative for biofilm production by congo red agar method. Of the four S. aureus isolates, two (50%) showed the presence of icaA gene. Of the 23 CONS isolates, three (13%) showed the presence of icaA gene. All the Pseudomonas isolates were negative for presence pslA (1119 bp) gene though most of them were phenotypically positive for biofilm formation. Conclusion: Most of the bacterial isolates obtained from contact lens wearers had the potential to produce biofilms. Tube method and Congo red agar method exhibited significant statistical correlation (P-value = 0.006) and picked up a good number of biofilm-forming isolates, hence may be used for detection of biofilm production. The absence of biofilm-forming gene did not rule out the possibility for phenotypic biofilm production by bacteria.